Organizing for Reform : Global Experiences - World Bank Group (World Bank, Washington, DC, 2020)
This note looks at the experience countries have had in introducing reforms that improved the business environment. Instead of examining what was done (that is, the content of reforms), the focus is placed on how reform programs came to be successful. The note aims to provide an overview of strategies and institutional mechanisms that help to: (i) successfully identify and prioritize reforms, and (ii) ensure successful reform implementation. The note provides a reference document with concrete examples that can be used and adapted by policymakers to address their specific challenges.